2015
DOI: 10.1155/2015/841645
|View full text |Cite
|
Sign up to set email alerts
|

Space-Time Analysis to Identify Areas at Risk of Mortality from Cardiovascular Disease

Abstract: This study aimed at identifying areas that were at risk of mortality due to cardiovascular disease in residents aged 45 years or older of the cities of Cuiabá and Várzea Grande between 2009 and 2011. We conducted an ecological study of mortality rates related to cardiovascular disease. Mortality rates were calculated for each census tract by the Local Empirical Bayes estimator. High- and low-risk clusters were identified by retrospective space-time scans for each year using the Poisson probability model. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…In Mato Grosso, burning of sugarcane forests and crops is the major source of air pollution, and these emissions have been responsible for causing diseases in people of different age groups [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In Mato Grosso, burning of sugarcane forests and crops is the major source of air pollution, and these emissions have been responsible for causing diseases in people of different age groups [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In the same region of the study, some authors observed an increase of morbidity and mortality during the same period. They approached that such advance is associated with increase of air pollutants related to the prevalence of biomass burns in the region 16,[29][30][31] . Urban waste burning, which is a common practice in Cuiabá and Várzea Grande, can also contribute to the concentration increase of air pollutants, as well as to their toxicity, because they present more proximity of the individual and have a great mixture of toxic components (plastic, fuel, electronic device) 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A purely spatial analysis was performed to identify high-risk clusters for CD mortality associated with high vehicular exposure, in which Bernoulli's probability model was used under a round ray of 1,713.86 meters 16 and considering a cluster of up to 50% of the risk population. The parameters used in this exam were: number of deaths per census tract (adjusted by gender, age, and income ratio) and plane coordinates (UTM Projection, South Fuse 21, metric units) of the centroids from the census tracts.…”
Section: Data Analysesmentioning
confidence: 99%
“…Urban space is effected by social and income inequality, increasing the tendency of shantytowns , violence and social exclusion and making access to health difficult 9 . Despite high levels of municipal human development, 20% of the people are vulnerable to poverty and 6% of the population have precarious housing conditions 10 .…”
Section: Population and Study Areamentioning
confidence: 99%